A Semiotic on the Headlines of Political Party’s Advertisements in Jakarta Post - Syaiful Bahri (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2018)
Language has a vital function in many different aspects such as social, military, economic, and even politics. Advertisement functions as media of promotion in transferring particular message from advertisers as the addressors to consumers as a target of the advertisement. The messages are meant to persuade consumers or people to choose a certain political party promoting its vision and mission. In addition, an advertisement covers all aspects of life as displayed in newspaper, television, direct mail, radio, magazines, internet and billboards.mIn this case, people can build a social community and use language as a means of delivering messages. This discusses one of the elements of political field as a subject matter of the discussion, the advertisements of political party in particular. In making advertisement, the political parties have to be creative in order to attract people‘s attention. With reference to the discussion of this research, the writer analyzes the advertisements of political parties major mass media.